The Development of Self Directed Learning Model (SDL) for Basic Competence in Analyzing Video, Animation AND/OR Digital Music - Syarifudin, Muhammad Nanda; Wibawanto, Hari; Syamwil, Rodia (Universitas Negeri Semarang, 2019)
One of the problems employing learning media is the incompetence in operation and application procedures. An apparent lack of using the audio video as a learning media causes by the teachers themselves. The purpose of the study is to arrange a model of self-directed learning (SDL) with audio-visual media to measure students’ result in terms of independence and proficiency that are valid, reliable and effective. Research and Development (R&D) method was employed to conduct the research with Four-D model of Thiagarajan. The eligibility of SDL model was tested with CVR in the aspect of validity, meanwhile the reliability was measured with Kappa statistics. The effectiveness of SDL was tested with t-test of dependent variable in terms of students’ independence and proficiency in operating the audio/video devices as learning media. The result showed that the validation of audio/video media, according to the three evaluators, was categorized into valid, the reliability was marked substantial, and the effectiveness of improvement related to students’ result in terms of independence and proficiency using SDL showed t-posttest 5,342, significantly, was effective to be employed. The conclusion of this study was that the SDL model with audio video media to acquire basic competence in analyzing video, animation and/or digital music production were reliable, eligible and effective, therefore could be applied.